2015
DOI: 10.1186/s12936-015-0812-2
|View full text |Cite
|
Sign up to set email alerts
|

Plasmodium transmission blocking activities of Vernonia amygdalina extracts and isolated compounds

Abstract: BackgroundMedicinal plants are a validated source for discovery of new leads and standardized herbal medicines. The aim of this study was to assess the activity of Vernoniaamygdalina leaf extracts and isolated compounds against gametocytes and sporogonic stages of Plasmodiumberghei and to validate the findings on field isolates of Plasmodium falciparum.MethodsAqueous (Ver-H2O) and ethanolic (Ver-EtOH) leaf extracts were tested in vivo for activity against sexual and asexual blood stage P. berghei parasites. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
32
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(35 citation statements)
references
References 67 publications
1
32
0
2
Order By: Relevance
“…Our research showed that methanol extracts of both plant species were equally effective against bruchids whereas earlier work (Mkenda et al 2015a) Furthermore, there is evidence that extracts are useful as antimicrobials (Erasto et al 2006;Orsomando et al 2016) and are toxic to parasitic protozoa (de Toledo et al 2014;Abay et al 2015) which would make them more useful to rural communities, particularly as they are easily cultivated. T. diversifolia is a globally invasive weed (Yang et al 2012) and a particular problem in Africa (Henderson 2007) where its collection and use as a pesticide could help reduce its environmental impacts.…”
Section: Discussionmentioning
confidence: 61%
“…Our research showed that methanol extracts of both plant species were equally effective against bruchids whereas earlier work (Mkenda et al 2015a) Furthermore, there is evidence that extracts are useful as antimicrobials (Erasto et al 2006;Orsomando et al 2016) and are toxic to parasitic protozoa (de Toledo et al 2014;Abay et al 2015) which would make them more useful to rural communities, particularly as they are easily cultivated. T. diversifolia is a globally invasive weed (Yang et al 2012) and a particular problem in Africa (Henderson 2007) where its collection and use as a pesticide could help reduce its environmental impacts.…”
Section: Discussionmentioning
confidence: 61%
“…The objective also includes the characterization of the as-synthesized nanoparticles. Both plants are known to be medicinal with various therapeutic benefits (Abay et al, 2015;Asante et al, 2016;Luo et al, 2011;Sinisi et al, 2016;Subarpriya, 2005). The synthesized silver nanoparticles were characterized by UV-Vis spectroscopy, FTIR and powder X-ray diffraction (PXRD).…”
mentioning
confidence: 99%
“…To assess in vitro transmission blocking (TB) activity of fractions and compounds targeted to early sporogonic development, the ookinete development assay (ODA) was employed as described in [19]. .…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Mice with parasitemia around 5% and with mature gametocytes were assessed for microgamete exflagellation. A drop of blood was taken from the mouse tail tip and diluted in exflagellation medium[19]; ookinete medium was prepared by adjusting exflagellation medium to pH 7.4 and by adding 20% heatinactivated fetal bovine serum and 1% penicillin (10.000 U) /streptomycin (10 mg/ml) before use. Blood samples diluted in exflagellation medium (1:25) were placed in hand-made coverslip glass slide chambers and incubated for 20 minutes at 19 °C.…”
mentioning
confidence: 99%